Validity and reliability of the Romanian version of the Hill-Bone compliance to high blood pressure therapy scale - Rusu, Răzvan-Nicolae; Gavril, Radu Sebastian; Ababei, Daniela Carmen; Macadan, Ioana; Ciobîcă, Andrei; Nicolae, Camelia; Popescu, Răducu Ionuț; Bild, Walther; Bild, Veronica (Frontiers in Pharmacology, 2024)
Romania is considered a country with high cardiovascular risk, arterial hypertension and its complications accounting for about 60% of total deaths. The management of high blood pressure often involves a combination of both therapeutic regimens as well as lifestyle changes, to which patients have to be adherent. In order to assess patients adherence to professionals' recommendations, validated tools are needed. The aim of our study was to translate, culturally adapt and validate the Hill-Bone Compliance to High Blood Pressure Therapy Scale was translated, adapted and validated into Romanian. The study included 215 participants from Iasi, North-Eastern Romania. The internal consistency of the instrument was measured with Cronbach's alpha coefficient, while the construct validity was determined using exploratory factor analysis and principal component extraction with promax rotation. Sampling adequacy and appropriateness of data for factor analysis was measured using Kaiser-Meyer-Olkin (KMO) statistics and Bartlett's test of sphericity. Our statistical analysis revealed a Cronbach's alpha coefficient of 0.733 (73.3%) and a Kaiser-Meyer-Olkin (KMO) Measure of Sampling Adequacy of 0.697. The chi square test demonstrated that the overall perfect adherence was not significantly associated with the number of medications taken per day variable (p = 0.721). The Romanian version of the Hill-Bone Compliance to High Blood Pressure Therapy Scale demonstrated suitability for its use in evaluating adherence in the intended population.